2013
DOI: 10.1371/journal.pone.0067271
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of an Invasive Non-Native Annual Weed, Impatiens glandulifera, on Above- and Below-Ground Invertebrate Communities in the United Kingdom

Abstract: Vegetation community composition and the above- and below-ground invertebrate communities are linked intrinsically, though few studies have assessed the impact of non-native plants on both these parts of the community together. We evaluated the differences in the above- (foliage- and ground-dwelling) and below-ground invertebrate communities in nine uninvaded plots and nine plots invaded by the annual invasive species Impatiens glandulifera, in the UK during 2007 and 2008. Over 139,000 invertebrates were ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 52 publications
(59 reference statements)
3
44
0
Order By: Relevance
“…; Tanner et al . ). A previous experiment has shown that this inhibition could be attributed to allelopathic effects on seed germination of U. dioica , from either leaf extracts or root leachates (Gruntman et al .…”
Section: Methodsmentioning
confidence: 97%
“…; Tanner et al . ). A previous experiment has shown that this inhibition could be attributed to allelopathic effects on seed germination of U. dioica , from either leaf extracts or root leachates (Gruntman et al .…”
Section: Methodsmentioning
confidence: 97%
“…In a second set of experiments, we examined the predictions of the NWH by evaluating the germination success of U. dioica seeds collected at both the native and invasive ranges of I. glandulifera in response to either leaf extracts of –or soil trained with– invasive I. glandulifera . In all experiments, we used U. dioica as a target species because it not only shares similar habitats as I. glandulifera at both ranges and has been shown to be highly inhibited by it at its invasive range (Tickner et al , Tanner et al ), but also because it is a fierce competitor often dominating plant communities not occupied by I. glandulifera (Hejda and Pyšek , Taylor ). Urtica dioica therefore presents a preferable test species, whose response to I. glandulifera could represent a more general effect compared to poorer competitors (Vilà and Weiner ).…”
mentioning
confidence: 99%
“…Himalayan balsam can tolerate a wide range of environmental conditions, enabling the plant to rapidly form dense monocultures on wasteland, woodland, railways lines and particularly in riparian habitats. As well as directly reducing biodiversity (Hulme and Bremner 2006), especially amongst invertebrate communities (Tanner et al 2013), Himalayan balsam also lures pollinators away from native plants, decreasing the fitness of native species (Chittka and Schürkens 2001). River banks are laid bare by the weed after it dies back in the winter, which renders them more prone to erosion (Greenwood and Kuhn 2014).…”
Section: Impatiens Glandulifera Royle (Himalayan Balsam) (Balsaminaceae)mentioning
confidence: 99%